IMPLEMENTASI UNDANG–UNDANG PENGELOLAAN LINGKUNGAN HIDUP DALAM PELAKSANAAN PROGRAM PEMBANGUNAN YANG BERKELANJUTAN - Trisna, Nila (Jurnal Public Policy, 2018)
Implementation of development activities is an absolute thing that must be done by the government in order to realize the goals of national development to create general welfare. because of various development activities aimed at improving the welfare of mankind which often also have an impact on environmental change. the negative impact of the existence of this pemabangunan must be more careful to avoid a damage in the existing environmental order either the environment and social environment. In Indonesia special arrangements on environmental management are contained in Law Number 32 Year 2009. This new approach is very effective to encourage environmental conservation, supervision and conservation. Environmental interests must be considered globally and in the long term for the welfare of the Ummah humans.In its development, environmental order and social environment should always be considered in order not to bring various types of disasters. Therefore, the responsibility of all elements of society in maintaining the environmental and social environment is expected to create a better way of looking at the environment itself. Issues concerning environmental degradation must necessarily start to be taken into consideration in order to provide a new perspective in order to promote the existence of an environmental safeguard so that it can indirectly contribute to avoiding a more severe hazard to the development of human and living beings during this time inhabit the earth and the environment sustainability.Keywords : legal aspect, environmentally, sustainability.